The Protective Effect of Royal Jelly on Liver Tissue of Adult Female Rats with Experimental Polycystic Ovarian Syndrome - Zahra Gholipour; Vahid Nejati; Gholamreza Najafi; Zahra Karimpour; Fereshteh Khaneshi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2014)
Background and Objectives: Polycystic ovary syndrome (PCOS) is one of the common clinical disorders, which is observed in 5-10% of women in their reproductive age. Its clinical characteristics include anovulation, hyperandrogenism,hirsutism, and resistance to insulin. This study was carried out aiming at determiningthe protective effect of royal jelly on liver tissue in polycystic rats.   Methods: In this experimental study, 32 adult female Wistar rats were randomly divided into four 8-rat groups: 1) control group, which received just normal food and water; 2) experimental polycystic ovary syndrome (PCO) group, in them the syndrome was induced through intramuscular injection of a single dose of estradiol valerate, 4mg (0/4mL) per rat; 3) control royal Jell group, which orally received 90mg/kg royal Jelly daily, and 4) PCOS-royal Jelly group, in them PCOS was induced similar to the second group, and treated with royal Jelly similar to the third group. The treatment period was 63 days (9 weeks). At the end of the treatment period, blood samples were collected from all rats for biochemical analysis, then, their liver tissue were stained with hematoxylin-eosin and sudan black stains. Data were analyzed using one-way ANOVA and Tukey's test. Significance level was considered p<0.05.   Results: In this study, royal jelly decreased lipid reserves of liver cells and decreased the destructive effects of oxidative stress due to PCOS in liver tissue in the group of rats treated with royal jelly.   Conclusion: According to the findings of this study, royal jelly has a protective effect on liver tissue of polysictic rats.